Immunogenicity, Efficacy, and Safety of a Novel Synthetic Microparticle Pre-Erythrocytic Malaria Vaccine in Multiple Host Species - Thomas J. Powell; Jie Tang; Robert Mitchell; Mary E. DeRome; Andrea Jacobs; Naveen Palath; Edwin Cardenas; Michelle Yorke; James G. Boyd; Stephen A. Kaba; Elizabeth Nardin (Vaccines, 2023)
We previously reported a protective antibody response in mice immunized with synthetic microparticle vaccines made using layer-by-layer fabrication (LbL-MP) and containing the conserved T1BT* epitopes from the P. falciparum circumsporozoite protein. To further optimize the vaccine candidate, a benchtop tangential flow filtration method (LbL-by-TFF) was developed and utilized to produce vaccine candidates that differed in the status of base layer crosslinking, inclusion of a TLR2 ligand in the antigenic peptide, and substitution of serine or alanine for an unpaired cysteine residue in the T* epitope. Studies in mice revealed consistent superiority of the Pam3Cys-modified candidates and a modest benefit of base layer crosslinking, as evidenced by higher and more persistent antibody titers (up to 18 months post-immunization), a qualitative improvement of T-cell responses toward a Th1 phenotype, and greater protection from live parasite challenges compared to the unmodified prototype candidate. Immunogenicity was also tested in a non-human primate model, the rhesus macaque. Base layer-crosslinked LbL-MP loaded with T1BT* peptide with or without covalently linked Pam3Cys elicited T1B-specific antibody responses and T1BT*-specific T-cell responses dominated by IFNγ secretion with lower levels of IL-5 secretion. The Pam3Cys-modified construct was more potent, generating antibody responses that neutralized wild-type P. falciparum in an in vitro hepatocyte invasion assay. IgG purified from individual macaques immunized with Pam3Cys.T1BT* LbL-MP protected naïve mice from challenges with transgenic P. berghei sporozoites that expressed the full-length PfCS protein, with 50–88% of passively immunized mice parasite-free for ≥15 days. Substitution of serine for an unpaired cysteine in the T* region of the T1BT* subunit did not adversely impact immune potency in the mouse while simplifying the manufacture of the antigenic peptide. In a Good Laboratory Practices compliant rabbit toxicology study, the base layer-crosslinked, Pam3Cys-modified, serine-substituted candidate was shown to be safe and immunogenic, eliciting parasite-neutralizing antibody responses and establishing the dose/route/regimen for a clinical evaluation of this novel synthetic microparticle pre-erythrocytic malaria vaccine candidate.